A Retrospective Consideration of Recreational Family Storytelling Among Parents and Their Adult Children. Issue 4 (18th May 2016) - Gagalis-Hoffman, Kelly; Zabriskie, Ramon B.; Freeman, Patti A.
Abstract : The aim of this study was to determine the purpose and function of recreational family storytelling across the life span from the perspective of parents and their adult children. Twelve individuals were interviewed (six parents paired with one of their adult children). Questions focused on ascertaining the purpose and function of storytelling from the perspectives of parents and children in the same family unit. In these families storytelling created opportunities for family bonding. Storytelling accomplished its purpose of creating family bonds through five functions: being fun, dealing with difficult topics or situations, transferring beliefs and values as well as giving listeners role models to emulate, offering the opportunity to take new perspectives, and purposefully initiating closeness between family members. The purpose and function of storytelling in the family appeared to change across the life span.